Rezim Pelaporan Tahunan PPh Wajib Pajak Orang Pribadi dalam Kerangka Coretax: Analisis WPR–Governmentality atas PER-11/PJ/2025 - Warsidi Warsidi; Rini Widianingsih (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2025)
This article analyses PER-11/PJ/2025 as a policy document that operates as a regime node in the annual individual income tax return (SPT Tahunan PPh Wajib Pajak Orang Pribadi/WPOP) reporting regime under Coretax. The analysis focuses on how the document problematises compliance through data standardisation, channel standardisation, data pre-population (prefill), and acceptance discipline. The article applies an interpretive-critical “What’s the Problem Represented to be?” (WPR) strategy by starting from the “solutions” postulated in the text to extract problem representations, presuppositions, and representational effects. A governmentality lens is then used to map regulatory rationalities and the governing technologies through which those rationalities are operationalised. Findings highlight two regime engines: (i) the master–attachment architecture of the SPT as a modular data schema that turns compliance into a processable data package (compliance as legibility/regularity); and (ii) administrative acceptance gatekeeping based on channel, NPWP validity, and the examination of returns at the acceptance stage (formal/completeness review), which conditions proof of receipt and the consequence of being “deemed not to have filed.” The article operationalises the term “simpul rezim” for this reading and closes with self-problematization to mark the risk of analytic bias when compliance is read primarily as a matter of data format and procedural gatekeeping.